2022
DOI: 10.3390/polym14204406
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Electrospun PLLA/PTMC Scaffolds

Abstract: Poly(L-lactide) (PLLA) and PLLA/poly(trimethylene carbonate) (PTMC) scaffolds characterised by different PLLA:PTMC mass ratios (10:0, 9:1, 8:2, 7:3, 6:4 and 5:5) were prepared via electrospinning. The results showed that increasing the PTMC content in the spinning solution caused the following effects: (1) the diameter of the prepared PLLA/PTMC electrospun fibres gradually increased from 188.12 ± 48.87 nm (10:0) to 584.01 ± 60.68 nm (5:5), (2) electrospun fibres with uniform diameters and no beads could be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…59,[61][62][63][64]69,143,154 Besides, PLLA lacks flexibility, elasticity, and toughness, making it unsuitable for a self-expansive cardiac occluder skeleton. 155,156 To keep the mechanical strength of the occluder for its functioning, additional locking systems are required when PLLA is used as the skeleton material in both PLLA/PDLLA and Absnow occluders. 59,[61][62][63][64][65][66] Studies have shown that the hydrophobicity and acidic products of PLLA might affect cell adhesion.…”
Section: Poly-ε-caprolactonementioning
confidence: 99%
See 2 more Smart Citations
“…59,[61][62][63][64]69,143,154 Besides, PLLA lacks flexibility, elasticity, and toughness, making it unsuitable for a self-expansive cardiac occluder skeleton. 155,156 To keep the mechanical strength of the occluder for its functioning, additional locking systems are required when PLLA is used as the skeleton material in both PLLA/PDLLA and Absnow occluders. 59,[61][62][63][64][65][66] Studies have shown that the hydrophobicity and acidic products of PLLA might affect cell adhesion.…”
Section: Poly-ε-caprolactonementioning
confidence: 99%
“…[61][62][63][64]68,69,71,72 Various methods, such as surface treatment, chemical crosslinking, and blending with other materials can modify the mechanical properties, hydrophobicity, and degradation time of PLLA, making it one of the most promising candidates materials for both skeleton and fabric of bioabsorbable cardiac occluders. 143,155,[158][159][160][161] PDLLA is a copolymer composed of D-and L-lactic units its physical and biological properties can be adjusted by altering the proportions of L-and D-isomers. [162][163][164][165] Compared with PLLA, it has better flexibility, stretchability, and a faster degradation rate due to its irregular and completely amorphous structure.…”
Section: Poly-ε-caprolactonementioning
confidence: 99%
See 1 more Smart Citation
“…24 Alternatively, PTMC has been used to develop many elastomeric substrates that have been used for vascular, skin, and intestinal tissue engineering. 25 This material typically exhibits poor stability; however, it can be copolymerized with LA or CL to produce a stable and electrospinnable poly(trimethylene carbonate-co-L-lactide) (PTMC-LA) or poly(trimethylene carbonate-co-caprolactone) (PTMC-CL) copolymer, respectively. 26 The ratios of component polymers in PTMC-LA or PTMC-CL copolymers can be modified to change the mechanical properties or biodegradation rate of substrates produced from these copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…PLCL is an elastomeric copolymer of caprolactone (CL) and lactic acid (LA) but exhibits poor cell affinity due to its lack of surface cell recognition sites . Alternatively, PTMC has been used to develop many elastomeric substrates that have been used for vascular, skin, and intestinal tissue engineering . This material typically exhibits poor stability; however, it can be copolymerized with LA or CL to produce a stable and electrospinnable poly­(trimethylene carbonate- co - l -lactide) (PTMC-LA) or poly­(trimethylene carbonate- co -caprolactone) (PTMC-CL) copolymer, respectively .…”
Section: Introductionmentioning
confidence: 99%